Consumer experience of a flexible exercise participation program (FEPP) for individuals with multiple sclerosis: A mixed‐methods study. (28th September 2021) - Smith, Moira; Neibling, Bridee; Williams, Gavin; Birks, Melanie; Barker, Ruth
Abstract: Background and Purpose: The flexible exercise participation program (FEPP) is a novel intervention developed to enable individuals with multiple sclerosis (MS) participate and progress in an exercise or sport of their choice. The FEPP is underpinned by guidelines on aerobic exercise for individuals with MS and is supported by a physiotherapist using behaviour change techniques. As part of a FEPP feasibility trial, the aim of this nested study was to explore the experience of participation in the FEPP from the perspective of individuals with MS. The objectives were to (i) determine the acceptability of the FEPP and (ii) identify recommendations for improvement. Methods: A mixed methods study using a sequential explanatory design was conducted. Part I consisted of a quantitative participant survey. Survey data were analysed descriptively using SPSS and informed the protocol for part II – qualitative interviews. Interview data were analysed thematically using NVivo. Part III consisted of integration of quantitative and qualitative data to allow greater explanation of survey responses. Individuals with MS who had participated in the FEPP feasibility trial were invited to take part in the study. Results: The FEPP was highly acceptability to the 10 participants. Five themes emerged to describe the experience of participating in the FEPP: (i) exploring exercise boundaries, (ii) measuring energy, (iii) acknowledging accountability, (iv) adjusting to exercising in a pandemic and (v) sustaining participation. Recommendations for improving the FEPP included changes to energy level monitoring and incorporation of peer support mechanisms. Discussion: Participants found the FEPP highly acceptable and valued the flexibility to choose their own activity and the health professional support. Based on participant recommendations, future versions of the FEPP will include daily rather than weekly monitoring of exercise and peer support to further enable individuals with MS to find the right balance with exercise and sport.